Ampicillin Resistance and Outcome Differences in Acute Antepartum Pyelonephritis. (27th August 2008) - Greer, Laura G.; Roberts, Scott W.; Sheffield, Jeanne S.; Rogers, Vanessa L.; Hill, James B.; Mcintire, Donald D.; Wendel, George D.
Abstract : Objective . To measure the incidence of ampicillin-resistant uropathogens in acute antepartum pyelonephritis and to determine if patients with resistant organisms had different clinical outcomes. Study design . This was a secondary analysis of a prospective cohort study of pregnant women admitted with pyelonephritis, diagnosed by standard clinical and laboratory criteria. All patients received ampicillin and gentamicin. Results . We identified 440 cases of acute pyelonephritis. Seventy-two percent (316 cases) had urine cultures with identification of organism and antibiotic sensitivities. Fifty-one percent of uropathogens were ampicillin resistant. The patients with ampicillin-resistant organisms were more likely to be older and multiparous. There were no significant differences in hospital course (length of stay, days of antibiotics, ECU admission, or readmission). Patients with ampicillin-resistant organisms did not have higher complication rates (anemia, renal dysfunction, respiratory insufficiency, or preterm birth). Conclusion . A majority of uropathogens were ampicillin resistant, but no differences in outcomes were observed in these patients.